Implementation of physics inquiry learning in high school to improve students' conceptual understanding - Anggy Marthania Tatyanty Putri; Nuril Munfaridah; Sutopo Sutopo (Universitas Pendidikan Indonesia, 2025)
Open inquiry is a learning approach that gives students complete freedom to manage the entire investigation process independently. This study aims to investigate the implementation of inquiry-based learning in high school physics education to enhance students' conceptual understanding. The method employed is a systematic literature review, which analyzes 20 scientific articles published between 2017 and 2025, obtained from Google Scholar and the Publish or Perish databases. The analysis process was conducted using a bibliometric approach with VOSviewer software, which maps the relationships between studies, authors, and topics. The results of the review indicate that inquiry learning, whether guided, local, or technology-based, has proven effective in enhancing conceptual mastery, critical thinking skills, and promoting active student involvement in the physics learning process. The integration of formative assessment in this learning model also strengthens students' conceptual understanding by providing continuous feedback. This research concludes that inquiry learning, supported by a proper assessment strategy, can be a relevant and strategic approach to improving the quality of physics learning in high school and supporting the achievement of 21st-century competencies. Abstrak Open inquiry merupakan pendekatan pembelajaran yang memberikan kebebasan penuh kepada peserta didik untuk mengelola seluruh proses penyelidikan secara mandiri. Penelitian ini bertujuan untuk mengkaji implementasi pembelajaran inkuiri dalam pembelajaran Fisika di tingkat SMA guna meningkatkan pemahaman konseptual peserta didik. Metode yang digunakan adalah systematic literature review dengan menganalisis 20 artikel ilmiah yang dipublikasikan antara tahun 2017 hingga 2025, diperoleh dari basis data Google Scholar dan Publish or Perish. Proses analisis dilakukan melalui pendekatan bibliometrik menggunakan perangkat lunak VOSviewer, yang memetakan keterkaitan antar studi, penulis, dan topik. Hasil tinjauan menunjukkan bahwa pembelajaran inkuiri, baik terbimbing maupun berbasis lokal dan teknologi, terbukti efektif dalam meningkatkan penguasaan konsep, keterampilan berpikir kritis, serta keterlibatan aktif peserta didik dalam proses pembelajaran Fisika. Integrasi asesmen formatif dalam model pembelajaran ini juga memperkuat pemahaman konseptual peserta didik melalui pemberian umpan balik yang berkelanjutan. Jadi, kesimpulan penelitian ini yaitu pembelajaran inkuiri yang didukung oleh strategi asesmen yang tepat dapat menjadi pendekatan yang relevan dan strategis dalam meningkatkan kualitas pembelajaran Fisika di SMA serta mendukung pencapaian kompetensi abad ke-21. Kata Kunci: fisika; pemahaman konseptual; pembelajaran inkuiri